The aqueous chemistry of oxides - Bunker, Bruce C.; Casey, William Howard (Oxford University Press, 2016)
The Aqueous Chemistry of Oxides is a comprehensive reference volume and special topics textbook that explores all of the major chemical reactions that take place between oxides and aqueous solutions. The book highlights the enormous impact that oxide-water reactions have in advanced technologies, materials science, geochemistry, and environmental science.